1995
DOI: 10.2149/tmh1973.23.121
|View full text |Cite
|
Sign up to set email alerts
|

Virological Study on Dengue Epidemic in Vientiane Municipality, Lao PDR, 1994.

Abstract: In May 1994, an epidemic of dengue fever (DF) / dengue hemorrhagic fever (DHF) was reported in Ban Horn commune in Vientiane municipality. This was after a six-year period of non-epidemic DF/ DHF in the municipality. In early June, we collected 81 serum specimens from children with fever of unknown origin (FUO) in the commune. Of 81 specimens, 48 were taken from children within 5 days after the onset of FUO and subjected to dengue (DEN) virus isolation. Four strains of DEN-1 and 12 strains of DEN-2 viruses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Natural concurrent infection with dengue viruses may occur in highly endemic areas where different dengue serotypes have been transmitted for many years. Many cases of simultaneous infection by more than one arbovirus species in mosquito or human hosts have been documented elsewhere 5,9,12,13,17,26 , and our laboratory has already reported one case of dengue 1 and 2 co-infection in a patient with mild infection 23 .…”
Section: Discussionmentioning
confidence: 81%
“…Natural concurrent infection with dengue viruses may occur in highly endemic areas where different dengue serotypes have been transmitted for many years. Many cases of simultaneous infection by more than one arbovirus species in mosquito or human hosts have been documented elsewhere 5,9,12,13,17,26 , and our laboratory has already reported one case of dengue 1 and 2 co-infection in a patient with mild infection 23 .…”
Section: Discussionmentioning
confidence: 81%
“…Currently, major environmental transformations are occurring in the periphery: what we call the ‘second urbanized belt’ has now became favourable to mosquito breeding. This view is supported by the 1994 study of Sisouk et al (1995) that reported an outbreak of DF/DHF for the first time in a rural neighbourhood (in Hatxaifong district) of Vientiane municipality. Historically, DF has been reported as occurring predominantly among urban populations.…”
Section: Discussionmentioning
confidence: 84%
“…The first case of dual infection with DENV-1 and DENV-2 was a resident in Vientiane, the capital of Laos, who was presented with mild symptoms of dengue, which were not severe enough to require admission [6]. Since then, there have been no further reports of dual DENV infections in Laos.…”
Section: Discussionmentioning
confidence: 99%
“…DENV serotypes responsible for such infections in Laos were first confirmed in 1994, and a case involving co-infection with two DENV serotypes was reported [6]. Since then, larger epidemics caused by all four serotypes have occurred [7, 8].…”
Section: Introductionmentioning
confidence: 99%